Sarcastic or Assertive: How Should Brands Reply to Consumers' Uncivil Comments on Social Media in the Context of Brand Activism?. Issue 1 (February 2022) - Batista, Juliana Moreira; Barros, Lucia S. G.; Peixoto, Fabricia V.; Botelho, Delane
Brands are increasingly embracing social activism and adopting positions on controversial issues, prompting some consumers to react by making uncivil comments on social media. How should brands reply to such incivility while maintaining their positions and protecting their reputations? Two common types of reply include either a sarcastic or an assertive tone, but the effects of these types of communication on consumers' attitudes toward brands remain largely unexplored. Results from a series of five studies exploring different causes (LGBT+ phobia, sexism, and racial equity) show that consumers evaluate brands that reply using an assertive tone more favorably than those using a sarcastic tone, which can be partially explained by the perceived aggressiveness of sarcasm. Additionally, support for a brand's stance acts as a boundary condition on the effect the type of reply adopted by the brand has on consumer attitudes toward the brand. So, the more someone supports a brand's stance, the less their perception of aggressiveness will negatively influence their attitude to that brand. We discuss the implications of these findings for marketing theory and practice.